Adsorption of Methyl Orange Dye onto Raw Maize Cob and Maize Cob Activated Carbon: Isotherms and Thermodynamic Studies - Ibrahim Abubakar, Safiyya; Adamu Ibrahim, Muhammad; Bashir Ibrahim, Muhammad (International Journal of Advanced Chemistry, 2020)
This study was aimed to evaluate the adsorption of Methyl orange (MO) onto raw maize cob (RMC) and maize cob activated carbon (MCAC) from aqueous solution using batch adsorption studies. The produced adsorbents were characterized by Scanning electron microscope (SEM), and Fourier transform infrared spectroscopy (FTIR). The influence of contact time, dosage, concentration, temperature, and pH were investigated as well as Isotherm and Thermodynamic studies. Effect of contact time showed that Methyl orange adsorption were found to reach equilibrium within 125 and 110 minutes with optimum percentage removal of about 86.98% and 94.57% for raw maize cob and maize cob activated carbon respectively. The dye removal efficiency was found to increase with increasing initial dye concentration from 10 mg/L to 100 mg/L, and adsorption efficiency was found to be high at lower pH. However, increase in the dosage of the adsorbents lead to the increase in the adsorption process. The equilibrium adsorption data were analyzed using four adsorption models: Langmuir, Freundlich, Temkin, and D-R. The results revealed that MO with raw maize cob and maize cob activated carbon fit well to Freundlich with R2 value 0.977 and Temkin with R2 value 0.990 respectively and mean adsorption energy calculated from D-R shows it is physical adsorption and also values of enthalpy and Gibbs free energy proves that. Values of activation parameters such as free energy changes (âˆ†G), enthalpy change (âˆ†H) and entropy change (âˆ†S) were calculated using Van't Hoff equation. All âˆ†G values were negative indicating that the adsorption was feasible and spontaneous. The result indicated that RMC and MCAC can be used for removal of MO from aqueous solution. The maize cob waste which is discarded as waste material was found to be effective adsorbent for the removal of Methyl orange dye from aqueous solution.Â Â